Impact of sitagliptin combination therapy and hypoglycemia in Japanese patients with type 2 diabetes: a multi-center retrospective observational cohort study - Tomoyuki Saito; Hirotoshi Ohmura; Shuko Nojiri; Hiroyuki Daida (Journal of Pharmaceutical Health Care and Sciences, 2020)
Abstract Background Patients with diabetes are at higher risk of developing polypharmacy because of the high frequency of comorbidities. There have been several reports on the hypoglycemic risk of the combination of hypoglycemic agents and other medications. This study aimed to investigate the hypoglycemic risk of drug-drug interaction between sitagliptin and other oral hypoglycemic agents or antihypertensive agents in Japanese patients with type 2 diabetes. Methods From January 2010 to March 2012, a total of 3247 patients were recruited and evaluated at outpatient clinics at Juntendo University Hospital, other satellite hospitals, and private clinics. This study was a sub-analysis of the Sitagliptin Registration Type 2 Diabetes-Juntendo Collaborating Project. Participants were limited to those treated with oral hypoglycemic agents, excluding insulin users, to investigate the association of the first hypoglycemic events with oral hypoglycemic agents or other medications within 6 months after starting sitagliptin. The factors related to the first hypoglycemic event were analyzed using Cox regression analysis. Results In total, 2956 patients with a mean age of 65.1 ± 11.3 years were included. A total of 46 hypoglycemic events (1.6%) were observed. One patient had severe hypoglycemia followed by emergency transport to the hospital. Sitagliptin was not associated with hypoglycemia, but its combination with sulfonylurea (hazard ratio: 4.42, 95% confidential interval: 1.36–14.42) or β-blocker (hazard ratio, 3.50, 95% confidential interval: 1.54–7.96) was significantly associated with hypoglycemia. Conclusions The drug-drug interactions between sitagliptin and sulfonylurea or β-blocker likely increases the hypoglycemic risk in Japanese patients with type 2 diabetes. Pharmacists should consider potential adverse events from drug-drug interaction in type 2 diabetes with polypharmacy, particularly those who are managed by several doctors or clinics.